Dynamic spectrum allocation scheme for heterogeneous network: BER analysis - Othman, Nurzati Iwani; Ismail, Ahmad Fadzil; Hasan, Mohammad Kamrul; Hashim, Wahidah; Badron, Khairayu (Universiti Teknikal Malaysia ( UTEM), 2017)
The latest advancement in wireless communication technology enables mobile users to communicate with each other more easily and at a very high speed. With the developed technology that encourages fast delivery of data and signal, mobile users can experience the best kind of service provided by the network operators. However, with the increasing number of users in an area that consists of femtocell and macrocell users, the data and signal transmission can sometimes be corrupted with the presence of cross-tier interference. This interference occurs when the femtocell and macrocell operate in the same carrier frequency. Therefore, such interference mitigation method must be implemented in order to maximize the throughput and increase the spectral efficiency of a wireless network. In this paper, a Dynamic Spectrum Allocation (DSA) scheme is proposed in order to correlate with the bit error rate, which will in turn contribute to throughput maximization factor in a heterogeneous network.